2017
DOI: 10.1159/000478067
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Trimetazidine on PDCD4/NF-κB/TNF-α Pathway in Coronary Microembolization

Abstract: Background/Aims: The local inflammatory response caused by coronary microembolization (CME) is the primary cause of progressive cardiac dysfunction. The PDCD4/NF-κB/TNF-α signaling pathway plays a significant role in CME-induced myocardial Inflammation. Trimetazidine (TMZ) reduces myocardial injury, caused by percutaneous coronary intervention, through relieving the CME-induced myocardial systolic dysfunction. Therefore, the present study investigated the role of TMZ pre-treatment in the protection of myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 22 publications
(20 reference statements)
0
13
0
1
Order By: Relevance
“…Additionally, a deeper analysis of the effects of TMZ during C2C12 differentition shows that the transcript levels of factors involved in myotube hypotrophy, namely atrogin-1/MAFbx and myostatin, decrease in TMZ-treated C2C12 myoblasts cultured in DM for 24h, to progressively return to control levels at 48h and 72h (Figure 4E ), while MuRF-1 mRNA levels are not affected by TMZ in the same conditions (Figure 4E ). We speculate that, since TMZ inhibits NF-kB [ 53 , 54 ] which is related to Atrogin expression, this might cause a reduction of Atrogin [ 55 ]. However, this point needs to be elucidated by additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a deeper analysis of the effects of TMZ during C2C12 differentition shows that the transcript levels of factors involved in myotube hypotrophy, namely atrogin-1/MAFbx and myostatin, decrease in TMZ-treated C2C12 myoblasts cultured in DM for 24h, to progressively return to control levels at 48h and 72h (Figure 4E ), while MuRF-1 mRNA levels are not affected by TMZ in the same conditions (Figure 4E ). We speculate that, since TMZ inhibits NF-kB [ 53 , 54 ] which is related to Atrogin expression, this might cause a reduction of Atrogin [ 55 ]. However, this point needs to be elucidated by additional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Trimetazidine has anti-inflammatory effects and has been shown to significantly decrease the levels of serum inflammatory markers (IL-1 β, IL-6, and TNF-α) (Zhou et al, 2012). In the model of coronary artery microembolism in Guangzhou Bama miniature pigs, inflammatory markers, such as PDCD4, NF-kB, and TNF-α, were shown to increase by 4-8 fold (Su et al, 2017) and were shown to decrease by about 40% following treatment with trimetazidine. Trimetazidine combined with coenzyme Q10 is effective against viral myocarditis (Shao et al, 2016) and alleviates septic myocardial damage induced by endotoxin by activating sirt1 (Chen et al, 2016) and promoting the migration of central granulocytes (Chen et al, 2018).…”
Section: Myocardial Inflammationmentioning
confidence: 98%
“…Previous studies showed that the expression of PDCD4 suppresses NF-kB transcriptional activation by inhibiting localization of p65 (Hwang et al, 2014;Su et al, 2017). To confirm whether the over-expression of PDCD4 reduces the nuclear translocation of the NF-κB subunit, we fractionated the cell lysates over-expressing PDCD4 into nuclear and cytoplasmic fractions, and then tested the subcellular localization of NF-κB subunits, viz.…”
Section: Pdcd4 Regulates Expression Of Il-5 Ccl-5 Vegf and Cxcl10mentioning
confidence: 99%